Safety and efficacy of manual small-incision cataract surgery in patients with brunescent and black cataracts and other ocular comorbidities - Manju Gajraj; Amit Mohan (Indian Journal of Ophthalmology, 2022)
Purpose: To determine the safety and efficacy of manual small-incision cataract surgery (MSICS) for brunescent and black cataracts in patients with other ocular comorbidities. Methods: Medical records of patients with hard cataracts (grade 4 nuclear opalescence and above) with other ocular comorbidities such as spheroidal degeneration of the cornea (SDC), pseudoexfoliation (PXF), non-dilating pupil, and high myopia who underwent MSICS were retrieved retrospectively. Intraoperative and postoperative complications were noted. Preoperative and postoperative visual outcome comparisons were performed using paired t-tests. Statistical significance was set at P < 0.05. Results: A total of 124 cataract patients with brunescent or black cataracts and other ocular comorbidities underwent surgery during the study period. They ranged in age from 56 to 89 years (mean: 68.9 + 11.9 years), with 55.66% (n = 69) of the patients being female and 44.35% (n = 55) male. Of the 124 cases, 45.16% (n = 56) had SDC, 31.45% (n = 39) had PXF, 14.51% (n = 18) had non-dilating pupils, and 8.87% (n = 11) had high myopia. Preoperatively all patients had visual acuity <6/60. At 1 month postoperatively 77.4% of patients achieved good vision >6/18, 16.9% had a borderline vision (6/18–6/60), and 5.6% had a poor vision (<6/60). No serious complications were observed. One patient had posterior capsular rent in a case of high myopia, and two cases had zonular dialysis for pseudoexfoliation. Conclusion: MSICS with intraocular lens implantation is safe and effective in eyes with brunescent/black cataracts if associated with SDC, PXF, high myopia, and non-dilating pupils and provides good visual outcomes with minimal complications.